1993
DOI: 10.1111/j.1348-0421.1993.tb03182.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin‐Binding Proteins of a Human Oral Spirochete Treponema denticola

Abstract: Major polypeptides from a human oral spirochete Treponema denticola ATCC 33520 were examined to demonstrate their ability to bind to human plasma fibronectin by immunoblot analysis. Of three main polypeptides separated on sodium dodecyl sulfate polyacrylamide gels 53,000-daltons (53-kDa) and 72-kDa surface antigenic proteins and a 38-kDa axial flagellar protein showed the ability to bind to fibronectin, suggesting that fibronectin on host cells can mediate cytoadherence of T. denticola by its binding to the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 14 publications
1
32
1
Order By: Relevance
“…Its SDS-PAGE protein profile is very similar to the 52-kDa Pj described here. The 62-kDa Pa of T. pallidum ATCC 27087 and the 53-kDa Pk of T. denticola ATCC 33520 are also found to be their outer envelope proteins capable of binding to fibronectin (20,21,33,34). The cellular locations of the Pb, Pc, Pd, Pg, and Pi, each of which was not a single binding polypeptide in each strain, have not been determined at present because of limitations of the application of techniques similar to that described above.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its SDS-PAGE protein profile is very similar to the 52-kDa Pj described here. The 62-kDa Pa of T. pallidum ATCC 27087 and the 53-kDa Pk of T. denticola ATCC 33520 are also found to be their outer envelope proteins capable of binding to fibronectin (20,21,33,34). The cellular locations of the Pb, Pc, Pd, Pg, and Pi, each of which was not a single binding polypeptide in each strain, have not been determined at present because of limitations of the application of techniques similar to that described above.…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin, laminin, and collagen are extracellular matrix components which mediate the binding of some Gram-positive and Gramnegative bacteria to host cells (2,4,5,7,9,13,30,37). Recently, we have reported that the 53-kDa and 72-kDa outer envelope proteins of T. denticola ATCC 33520 can bind to fibronectin, suggesting that fibronectin may mediate adherence of this spirochete to gingival tissues in vivo (34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specific attachment to the extracellular matrix (ECM) component fibronectin has been documented for many pathogenic bacteria, including the related spirochetes Borrelia burgdorferi (19,35), Leptospira interrogans (26), and Treponema denticola (8)(9)(10)49). Fibronectin is also likely to be involved in T. pallidum cytoadherence.…”
mentioning
confidence: 99%
“…Previous studies focused on potential adhesins (37,47) and on spirochete surface proteins (21,52,66) or other cellular components (11,35) cytotoxic to eukaryotic cells. Studies of membrane-associated proteins of two distinct strains of T. denticola identified a 70-kDa protein having fibronectin (FN)-binding (67) or FN-, laminin-, and fibrinogen-binding (37) activity. This protein was distinct from the 53-kDa Msp pore-forming adhesin in these strains, which also bound FN (23,37,67).…”
mentioning
confidence: 99%